Studies on drying of fish using a BARC - TYPE solar dryer. - Vimaladevi S (Department of Processing Technology,College of Fisheries, 2011)
A study was conducted with the aim of evaluating the drying efficiency of a newly designed solar dryer (modified BARC type) in comparison with conventional sun drying. The materials used for drying were beheaded prawn (Metapenaeus dobsoni) and salted fish (Cynoglossus macrostomus). Rate of drying was found to be influenced by the atmospheric temperature and humidity, either using dryer (test or by sun drying (control). In the case of prawn, the drying period was 7h by dryer compared to control which took about 10h whereas in the case of fish it was only 7h compared to control which took about 9h. Various parameters such as moisture content, water activity, TPC, TFC, TVBN content and PV, during drying were monitored. The quality variations in prawn or fish were significantly lower when dried using the solar dryer compared to direct sun drying. Sensory evaluation based on colour, odour, texture and taste, also proved that the solar dried samples were of superior quality compared to control. Sorption isotherm for test and control did not vary much in shape for both prawn and fish. This indicates that the effect of the type of drying on the bound water of the products. For conducting storage studies the dried prawn and dry salted fish, both test and control, were packed in low permeable polypropylene- polyamide bags and stored at room temperature for about 80 days. Quality parameters, viz., moisture content and water activity, TPC, TFC, TVBN content, PV and sensory evaluation based on colour, odour, taste and texture were evaluated during storage. Both test and control samples remained acceptable throughout the storage period. However, the quality of prawn or fish dried in solar dryer was found to be superior compared to their respective sun dried control samples. The additional cost was only Rs 2.40/ kg for dried prawn and Rs 2.00/ kg for dry salted fish. The equipment is recommended for small scale production of dried products.